ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT UNDERPRICING SAHAM PADA PERUSAHAAN YANG MELAKUKAN INITIAL PUBLIC OFFERING DI BEI - Junaeni, Irawati (Jurnal Ilmiah Widya, 2013)
In order to develop the business, lot of companies conducts variety of ways to get their capital needs. One of them is by increasing the number of shares by issuing new shares. This can be done by launched offering of company’s shares in Indonesia stock exchange. An offering of company's shares to the public through the stock exchange called 'go public', while an initial public offering of the shares called Initial Public Offering (IPO.) This research aims to analyze the factors affect of shares allegedly under pricing on company who launched an IPO in Indonesia stock exchange during 2006-2010. The research method descriptive analysis which the dependent variable is the level of under pricing shares, while Independent variables are underwriter reputation, financial leverage, proceeds, and industrial type. The research used multiple regression models to test the relationship between dependent and independent variable. The hypothesis was tested using statistical methods in multiple regression models to find out whether linear factors simultaneously or partially influence the degree of under pricing shares. The testing done shows partially, indicate that only reputation of underwriting having a significant affect to under pricing. Whereas by simultaneously financial leverage, proceeds, and industrial type obtained result have significant affect to under pricing.